A cara da morte: imaginário fúnebre no relato de sepultadores de São Paulo - Franco, Clarissa de (2008)
The main objective of this study is to research the components of the universal imaginary that represents death and how this imaginary reverberates in the reports and the content of the dreams of grave-diggers in five cemeteries in the city of Sao Paulo. By imaginary, we mean the "connector" between the internal and external environments of human beings, through the symbolic and imagistic language. Our hypothesis was based on the possible existence of an archetypical imaginary of death, with elements that transpose historic moments. We also assume that, because grave-diggers work directly with the grossly material side of death the visual impact of the corpse, the dirt and the smell of the decomposing body and because they play an important role in the painful rite that the deceased one´s family goes through, they would be exposed to an intense unconscious experience of feelings related to death, in contrast to apparent posture of denial. We tried to investigate this intensity of emotional contents through semi-directed interviews and questionnaires, looking for reports of beliefs and feelings about dying. We also heard reports of dreams, which supported the presence of emotion-laden imaginary elements related to death, as well as archetypical contents in different cultures, as had been originally hyppothesized. We worked with grave-diggers of the Araçá, Consolação, Lapa, Vila Mariana and Vila Nova Cachoeirinha cemeteries